Quality of Life and its Related Factors among Elderly People - Parvin Cheraghi; Zahra Eskandari; Shiva Bozorgmehr; Nasibeh Zanjari; Zahra Cheraghi (Hamadan University of Medical Sciences, 2019)
Aims: Considering the increase of the elderly population, it is essential to investigate the social, physical and mental health of the elderly, which is related to their quality of life. The present study was conducted to assess the quality of life of elderly people in Hamedan province, Iran. Instruments & Methods: This descriptive cross-sectional research was carried out among 238 elderly males and females aged over 60, who referred to the health centers of Hamedan province. The subjects were selected using randomized stratified sampling method. The 36-item questionnaire (SF-36) was used to evaluation the dimensions of quality of life of the subjects. Data were analyzed using STATA 13 software through the independent T-test and one-way analysis of variance. Findings: The highest mean of quality of life was reported in the physical dimension and the subscale of pain (70.86±21.29) and the lowest mean was reported in the general health (24.10±89.29). The quality of life score in the subscales of physical and mental health dimensions in males was higher than the females, which this difference was statistically significant (p<0.05). Also, in the subscales of physical and mental health, the mean score of quality of life was higher in the married subjects and the subjects with higher education (p<0.05). Conclusion: The mean of quality of life in the dimensions of physical and mental health and their related subscales in the elderly people of Hamedan province is at the acceptable and moderate level and the lowest score is related to the general health. The quality of life is also lower in elderly females, and elderly people with low education, and single elderly people.